Laboratorium Bimbingan Konseling Pengembangan Life Skill Anak Berbasis Komunitas Guru dan Anak Disabilitas pada Sekolah Luar Biasa Negeri 14 Takengon Kabupaten Aceh Tengah - Hafidz Awlawi, Addahri; Umar, Ali (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
Children with special needs (Heward) or ABK are children with special characteristics that are different from children in general without always showing mental, emotional or physical disabilities, which are included in ABK, including: blind, deaf, mentally retarded, quadriplegic, hearing impaired, learning difficulties, behavioral disorders, gifted children, children with health problems. Life skills have many definitions and are often misinterpreted, only limited to the skills of producing something, for example, handicrafts, weaving and so on. The purpose of this service is to increase the level of relevance between education and real life, so that after graduating or graduating from a special school or special school, children with special needs are expected to be more independent. The method used in this service is by way of lectures, demonstrations, questions and answers and training on the implementation of Life Skills life skills education for children with special needs, namely by delivering material, educational games, and motor games. The result of this service is that children with special needs become more enthusiastic about participating in activities because the activities are not monotonous and not boring. Children with special needs also show proficiency in every activity they carry out. Children become more capable of forming good life skills.